2019
DOI: 10.1038/s41467-019-09089-x
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of lipid specificity within Ups/PRELI lipid transfer proteins

Abstract: Conserved lipid transfer proteins of the Ups/PRELI family regulate lipid accumulation in mitochondria by shuttling phospholipids in a lipid-specific manner across the intermembrane space. Here, we combine structural analysis, unbiased genetic approaches in yeast and molecular dynamics simulations to unravel determinants of lipid specificity within the conserved Ups/PRELI family. We present structures of human PRELID1-TRIAP1 and PRELID3b-TRIAP1 complexes, which exert lipid transfer activity for phosphatidic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 51 publications
(87 reference statements)
0
49
2
Order By: Relevance
“…For instance, the fibroblast growth factor receptor 4 (FGFR4) gene is a transmembrane tyrosine kinase receptor that may play essential roles in the regulation of hepatic bile acid and lipid metabolism [ 53 ]. PRELID1 (PRELI Domain Containing 1), another gene located in the same region, is a protein-coding gene that regulates lipid accumulation in the mitochondria by shuttling phospholipids in a lipid-specific manner across the intermembrane space [ 54 ]. Other important genes within this window include HK3 (Hexokinase 3), which is crucial for glucose metabolism pathways and phosphorylates glucose to produce glucose-6-phosphate; the RGS14 (Regulator of G Protein Signaling 14) gene, which encodes a member of the regulator of G-protein signaling family and as a GTPase activating protein (GAP), it increases the rate of conversion of GTP to GDP; PDLIM7 (PDZ and LIM domain 7), which is known to regulate muscle development and function, and associates with—and localizes to—actin filaments in fibroblasts via its PDZ domain [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the fibroblast growth factor receptor 4 (FGFR4) gene is a transmembrane tyrosine kinase receptor that may play essential roles in the regulation of hepatic bile acid and lipid metabolism [ 53 ]. PRELID1 (PRELI Domain Containing 1), another gene located in the same region, is a protein-coding gene that regulates lipid accumulation in the mitochondria by shuttling phospholipids in a lipid-specific manner across the intermembrane space [ 54 ]. Other important genes within this window include HK3 (Hexokinase 3), which is crucial for glucose metabolism pathways and phosphorylates glucose to produce glucose-6-phosphate; the RGS14 (Regulator of G Protein Signaling 14) gene, which encodes a member of the regulator of G-protein signaling family and as a GTPase activating protein (GAP), it increases the rate of conversion of GTP to GDP; PDLIM7 (PDZ and LIM domain 7), which is known to regulate muscle development and function, and associates with—and localizes to—actin filaments in fibroblasts via its PDZ domain [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thylakoid lipids provide a bilayer matrix to support the proteolipid heterooligomeric complexes and, as a result of their hydrophobicity and low dielectric constant, facilitate generation of a transmembrane proton electrochemical gradient coupled to electron transport (3). In addition, the lipids function as essential structural components in the photosynthetic complexes, inferred from high-resolution crystal structures (4 -10) and MS analyses (11)(12)(13)(14)(15)(16). All four classes of lipids have been implicated in the biogenesis of the thylakoid membrane (3).…”
mentioning
confidence: 99%
“…We discovered that residues W65 and F69 of the α2-loop would be inserted into the membrane alternately during PA transfer. Although Miliara et al suggested that the α3-helix and the Ω-loop (here, α2-loop) undergo subtle conformational changes, potentially contributing to phospholipid binding and release 26 and speculated that conformational differences in the Ω-loop (here, α2-loop) and α3helix between PRELID1 and PRELID3b are potentially important for lipid specificity 23 , no experimental data have supported this finding. Our disulfide-bridge experiments not only verified these conformational changes but also suggest a synergistic conformational change between the α2-loop and N-α3-helix.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous crystal structures of Ups1/Mdm35 (or its homologs) in different states have been reported 17 , 18 , 21 , 23 , the mechanism underlying PA transfer between mitochondrial membranes remains elusive. Here, we reported two new crystal structures of Ups1/Mdm35, performed all-atom simulations of Ups1-membane and Ups1/Mdm35-membrane, and various biochemical and biophysical experiments, revealing how Ups1/Mdm35 interacts with the membrane and potential conformational changes of Ups1 during PA transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation